A função do fator de inibição da migração de macrófagos (MIF) no controle da infecção por Toxoplasma gondii em células trofoblásticas é dependente da idade gestacional - Gomes, Angelica de Oliveira (2013)
Because macrophage migration inhibitory factor (MIF) is a key cytokine in pregnancy and has a role in inflammatory response and pathogen defense, the objective of the present study was to investigate the effects of MIF in first- and third-trimester human placental explants infected with Toxoplasma gondii; as well as to find up the mechanisms of MIF action. Methodology: For in vitro assay human explants were treated with recombinant MIF, IL-12, interferon-, transforming growth factor-1, or IL-10, followed by infection with T. gondii RH strain tachyzoites. Supernatants of cultured explants were assessed for cytokines by ELISA. Explants were processed for morphologic analysis, immunohistochemistry, real-time PCR analysis and western blotting. In addition, for in vivo assay C57BL/6 MIF-/- and C57BL/6 WT females were orally infected with T. gondii ME-49 strain on day 1 of pregnancy and were sacrificed on day 8 post infection. The controls were set up with non pregnant or/and non infected mice. The uteri were evaluated by western blotting analyses and cytokines were assed in serum by CBA assay. Results: Comparison of infected and stimulated explants versus noninfected control explants demonstrated a significant increase in MIF release in first-trimester but not third-trimester explants. Tissue parasitism was higher in third- than in first-trimester explants. Moreover, T. gondii DNA content was lower in first-trimester explants treated with MIF compared with untreated explants. However, in third-trimester explants, MIF stimulus decreased T. gondii DNA content only at the highest concentration of the cytokine. In addition, high expression of MIF receptor was observed in first-trimester placental explants, whereas MIF receptor expression was low in third-trimester explants. In vivo assay demonstrated that the C57BL/6 MIF-/- presented high IDO and low COX-2 expression in the uteri and an increased release on cytokines of Th2 profile in response to infection associated with pregnancy. On the other hand C57BL/6 WT presented low IDO and high COX-2 expression in the uteri and an increased release on cytokines of Th1 profile in response to infection associated with pregnancy. Conclusion: MIF was up-regulated and demonstrated to be important for control of T. gondii infection in first-trimester explants, whereas lack of MIF up-regulation in third-trimester placentas may be involved in higher susceptibility to infection at this gestational age. The mechanism of MIF action in the maternal-fetal interface may be related with suppression of IDO and induction of pro-inflammatory immune response.